2012
DOI: 10.1038/nclimate1636
|View full text |Cite
|
Sign up to set email alerts
|

Promoting pro-environmental action in climate change deniers

Abstract: 603In the above Letter, we used the term 'denier' to describe people who are not convinced that anthropogenic climate change is occurring. The denier label refers to an image held by some in the mainstream climate science community that such people are contrarian, which other terms like 'sceptic' do not capture. We hoped our findings would suggest to mainstream climate scientists the benefit of looking beyond this contrarian image, by showing that deniers were more supportive of actions to address climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
138
4
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(153 citation statements)
references
References 1 publication
9
138
4
2
Order By: Relevance
“…Coupling, for example, values around security or freedom with self-transcending values like concern for the welfare of others is one possible way of resolving the tension between the social marketing and 'common cause' approaches to campaigning, and making best use of the available academic evidence. 103,104 In addition, it is now well established that communication strategies based on 'one way' message-oriented communication tend to be ineffective at fostering significant and sustained behavioral engagement 87,105,106 They may also promote polarized views through 'biased assimilation' of the message content by opposing attitudinal groups. 107 The habits and social practices of individuals and groups provide the context in which valuebased messages are received, yet the vast majority of public communication around climate change has involved individuals, and not much consideration of the social context.…”
Section: Values and The Framing Of Campaigns About Climate Changementioning
confidence: 99%
“…Coupling, for example, values around security or freedom with self-transcending values like concern for the welfare of others is one possible way of resolving the tension between the social marketing and 'common cause' approaches to campaigning, and making best use of the available academic evidence. 103,104 In addition, it is now well established that communication strategies based on 'one way' message-oriented communication tend to be ineffective at fostering significant and sustained behavioral engagement 87,105,106 They may also promote polarized views through 'biased assimilation' of the message content by opposing attitudinal groups. 107 The habits and social practices of individuals and groups provide the context in which valuebased messages are received, yet the vast majority of public communication around climate change has involved individuals, and not much consideration of the social context.…”
Section: Values and The Framing Of Campaigns About Climate Changementioning
confidence: 99%
“…Wetland restoration is one method with which northern countries could aim to meet their GHG targets under the Kyoto Protocol (Bain, Hornsey, Bongiorno, & Jeffries, 2012). In contrast to drainage, restoration raises the WT, increases water saturation, and thus may increase CH 4 emissions (Saarino, Winiwarter, & Leitao, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of social co-benefits can be seen in public health research that has emphasised that resilience projects, aimed towards improving preparedness for natural disasters, can enhance social capital by better connecting citizens to social networks and encouraging membership of community forums (Cheng & Berry, 2013: 307). Finally, a slightly more ambiguous social co-benefit has been explored by Bain et al (2012), Bain et al (2013) and Bain et al (2016) within research that has found that "motivations to act on climate change were clearly related to beliefs about co-benefits, especially … building a more caring and moral community." This co-benefit is socialpsychological in nature, reflecting a means of self-identification through which individuals perceive themselves to be people who want to part of an ethical society which functions in a benevolent manner (Bain et al 2016: 600).…”
Section: Climate Change Communication and The Discursive Potential Ofmentioning
confidence: 99%